Kualitas Terjemahan Teks Ilmiah Hasil Penerjemahan Mesin Google Translate dan Bing Translator - Abdullah Achmad (Program Studi Magister Linguistik Terapan UNJ, 2016)
The research purpose is to show the quality of the translated scientific text by Google Translate and Bing Translator. This research method is qualitative content analysis with comparative model. The title of the scientific text on educational is Students Perception of University Teaching Behaviours, published in Teaching in Higher Education Journal (Routledge in 2009). This research data are 279 sentences taken from the translated scientific text from English to Indonesian. All items are analysed by using assessment instruments of translation quality. The criteria are accuracy, readability, acceptability. The results of the research show that the quality of translated scientific text by Google Translate is less accurate, fairly readable, and less acceptable. Meanwhile, the translation by Bing Translator is less accurate, fairly readable, and not acceptable. The translation quality of scientific text by Google Translate is better than Bing Translator.